Exploring critical reflection in a virtual learning community in teacher education. Issue 3 (4th May 2021) - Miller, Libbi R.; Nelson, Frederick Peinado; Phillips, Emy Lopez
ABSTRACT: In this naturalistic study, we examined the reflective thinking of 39 pre-service teachers (PSTs) in an introductory curriculum, instruction, and technology course as they engaged in an online virtual learning community. Our framework considers both reflective thinking as revealed through individual posts to the community and dialogical interaction between PSTs as they comment on posts. Our research identified three themes in PST reflection: 1.) the presence of peer affirmation and support, 2.) the connection of PSTs experiences to content included in the course, and 3.) the presence of critical reflection. The study concludes that by providing provocative stimuli, meaningful content, and an interactive process for reflection, a VLC can create a space for members to move from their traditional comfort zones to a disruption of their normative beliefs about teaching, schools, and themselves.